Needs and early response towards internally displaced people in Hatay Province in the aftermath of the 2023 earthquake in Turkey - Guenter Froeschl; Buse Zagli; Ege Erucar; Kutaiba Alaaeddin; Mustafa El Othman; Cem Hatunoglu (BMC Public Health)
Abstract Background On 06 February 2023, an extreme earthquake affected Hatay province in Turkey. The immediate response consisted of medical teams focusing on traumatology and immediate trauma related care. In the intermediate time period, after days to weeks, more primary health care was needed for displaced populations in tent shelters and in surrounding villages. We are describing the results of a needs assessment intervention and health services provided by an international non-governmental organization. Methods Mobile teams circulated to displaced populations in peripheral locations. Fourty-two representatives of communities were interviewed for rapid needs assessment. After triaging and identification of needs, mobile medical units offered primary health care services. Data was collected digitally, directly by the healthcare workers on basic demographics and health conditions. We are reporting a descriptive overview of the data. Results Communities showed different degrees and dimensions of need, such as entirely lacking health services, or missing sanitary facilities. Populations in the communities increased in most sites. From 16 February to 06 April 2023, 3,027 patients were attended to. The majority of our beneficiaries were female (61.0%) and of Turkish origin (66.9%). Children under the age of 18 accounted for 41.3%. The most reported health findings were upper respiratory infections (24.9%) and scabies (9.7%). In 68 patients, a primary diagnosis of a mental health condition was made. Conclusions In the intermediate response after an earthquake-driven disaster, primary healthcare provision becomes a crucial element of humanitarian support. Massive displacement into crowded tent shelters lead to respiratory conditions and contagious ectoparasitism. Organizations engaging in this context need to be prepared accordingly, not the least by sufficient stock keeping.